Animation in Computer Graphics Using Regular Deformation - Periyanayagam, Rajan (2004)
Animation in computer graphics is implemented mostly by deforming solid objects. In this approach, dynamic motion is not coupled with deformation. In this proposed work, an attempt is made to deform surfaces to implement animation. Instead of deforming solid objects, deforming surfaces will take much less time as the number of graphic primitives (such as lines and curves) will be less compared to solid objects like spheres, cylinders etc. The main objective of this research work is to implement deformation of regular objects using OpenGL. Open GL codes are rarely found in the literature for implementing regular deformation.